Analysis of Series-Parallel Hybrid Electric Vehicle with Suitable DC-DC Converter for a Given Drive Cycle - Singh, Jasandeep (My University, 2016)
Due to depleting conventional energy resources, ongoing research and development area is focused on finding the alternates which are clean and efficient. In transport sector, as the fuel prices are consistently rising and simultaneously harmful emissions are causing serious environmental impacts, the automotive industry has shifted to the development of Hybrid Electric Vehicle/Electric Vehicle which overcomes the limitations and problems faced by conventional vehicles. Many automotive companies including Maruti, Mahindra, Toyota and Tesla are competing with each other in the field of HEV’s. The electrical system in the vehicle comprises mainly of battery source, dc-dc converter and the motor drive. The dc-dc converter is the key element in the Hybrid electric vehicle system which boosts the voltage level of battery to the rated voltage level of the motor drive and also helps in reducing the size of huge battery packs. Also during regenerative action, dc-dc converter is used to buck the generated voltage level to charge the battery bank. The thesis work started withstudyingvarious dc-dc converters including Buck, Boost, Buck-Boost, Push-pull and variousothers. Merits and demerits of the converters are analysed. Improved dc-dc converters including Z source and Trans z source dc-dc converters are simulated in MATLAB initially for resistance load. The Z source dc-dc converter is mathematically modeled using the State space averaging technique and its step response is plotted. Mathematical modeling using State space averaging technique is also performed for Trans Z source and bi-directional dc-dc converter. The work aimed at application of bidirectional DC-DC converters in Hybrid electric vehicle. The Bi-directional full bridge dc-dc converter is implemented in Series-Parallel hybrid electric vehicle model in SIMULINK. The closed loop speed controller using PI controller is used for achieving the speed demanded by the driver in terms of acceleration in motor and generator drives. It is also used for deciding the throttle values of ICE according to the power demanded by the drive train. The results include the analysis and discussion of various parameters including voltage, current, power and drive torque. The charging/discharging of battery for acceleration and deceleration modes of operation is also presented and justified.
Keywords: HEV,Bidirectional DC-DC Converter